2017
DOI: 10.1002/ejp.1001
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture and electro‐acupuncture for people diagnosed with subacromial pain syndrome: A multicentre randomized trial

Abstract: Background:Musculoskeletal disorders have been identified globally as the second most common healthcare problem for 'years lived with disability', and of these shoulder conditions are amongst the most common, frequently associated with substantial pain and morbidity. Exercise and acupuncture are often provided as initial treatments for musculoskeletal shoulder conditions but their clinical effectiveness is uncertain. This study compared group exercise with group exercise plus either acupuncture or electro-acup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 42 publications
(59 reference statements)
1
27
0
9
Order By: Relevance
“…5,17,73 Nevertheless, a recent multicenter randomized clinical trial 53 (n = 227) found that the addition of acupuncture or electroacupuncture was no more effective than exercise alone in the treatment of individuals with SAPS. However, in contrast to the current study, Lewis et al 53 included patients with full-thickness and/or massive irreparable rotator cuff tears, and therefore used a much broader and nonspecific definition of SAPS than other trials 2,7,31,32,47,63,68 and diagnostic guidelines. 14 Prior trials on dry needling for shoulder pain investigated intramuscular trigger point dry needling and needle pistoning techniques, resulting in inconsistent outcomes for meaningful changes in pain and disability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,17,73 Nevertheless, a recent multicenter randomized clinical trial 53 (n = 227) found that the addition of acupuncture or electroacupuncture was no more effective than exercise alone in the treatment of individuals with SAPS. However, in contrast to the current study, Lewis et al 53 included patients with full-thickness and/or massive irreparable rotator cuff tears, and therefore used a much broader and nonspecific definition of SAPS than other trials 2,7,31,32,47,63,68 and diagnostic guidelines. 14 Prior trials on dry needling for shoulder pain investigated intramuscular trigger point dry needling and needle pistoning techniques, resulting in inconsistent outcomes for meaningful changes in pain and disability.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, placement of up to 6 needles in the upper thoracic paraspinal, periscapular, and glenohumeral regions was optional and based on the findings from passive motion testing, the presence of localized myofascial trigger points, and/ or the presence of stiffness or pain during palpatory examination. Details regarding needle size, insertion site, angulation, depth, anatomical target, manipulation, 15,42,48,63,89 and electrical stimulation parameters 29,31,47,52,53,63,64 are summarized in APPENDIX A.…”
Section: Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PPAS is a valid, reliable, and simple-to-handle tool to assess the subjects’ apprehension to receive electrical stimulation therapy [37]. The exclusion criteria were as follows: Any contraindication to the use of IFT (Table 1) [38,39]; previous cervical spine or shoulder surgery; a history of neurological or mental illnesses; diagnosed central or peripheral nervous system diseases [23]; concomitant fracture in the neck/shoulder; altered sensitivity to tactile stimuli or loss of sensation in the neck/shoulder or upper extremity [6]; concomitant radiological diagnosis of osteoarthritis of the glenohumeral or acromioclavicular joints; fibromyalgia or rheumatoid arthritis [23]; having received injections of corticoids or hyaluronic acid following surgery; symptoms of frozen shoulder [40]; impaired cognition or communication; and being involved in an on-going medico-legal dispute.…”
Section: Methodsmentioning
confidence: 99%
“…Among shoulder complaints, subacromial pain syndrome (SAPS) is the most common disorder that result in loss of function, increased pain sensitivity [3], and impaired quality of life, accounting for up to 70% of consultations in primary care [4]. SAPS is characterized by persistent pain around the acromion, which usually worsens during or after lifting the upper extremity [5], and embraces clinical diagnosis such as subacromial impingement and rotator cuff tears [6]. The clinical course of SAPS remains unclear, and previous evidence suggests that 50% of adults with chronic SAPS may only recover after 10 to 18 months of initial onset [7].…”
Section: Introductionmentioning
confidence: 99%